Glycyrrhizic Acid-Induced Differentiation Repressed Stemness in Hepatocellular Carcinoma by Targeting c-Jun N-Terminal Kinase 1 - Cai, Shijiao; Bi, Zhun; Bai, Yunpeng; Zhang, Heng; Zhai, Denghui; Xiao, Cui; Tang, Yuanhao; Yang, Lan; Zhang, Xiaoyun; Li, Kun; Yang, Ru; Liu, Yanrong; et al. (Frontiers in Oncology, 2020)
Hepatocellular carcinoma (HCC) is one of the most common malignant cancers with poor prognosis and high incidence. Cancer stem cells (CSCs) play a vital role in tumor initiation and malignancy. The degree of differentiation of HCC is closely related to its stemness. Glycyrrhizic acid (GA) plays a critical role in inhibiting the degree of malignancy of HCC. At present, the effect of GA on the differentiation and stemness of HCC has not been reported, and its pharmacological mechanism remains to be elucidated. This study evaluated the effect of GA on the stemness of HCC and investigated its targets through proteomics and chemical biology. Results showed that GA can repress stemness and induce differentiation in HCC in vitro. GEO analysis revealed that cell differentiation was up-regulated while the pluripotency of stem cells was down-regulated after GA administration. Virtual screening was used to predict the it has been confirmed that GA enhanced the anti-tumor effects of sorafenib in HCC treatment. These results broadened our insight of the pharmacological mechanism of GA, and the importance of JNK1 as a therapeutic target for HCC treatment.